Effects of digital transformation in the oil and gas complex - O. V. Baykova; E. O. Gromyko (Вестник университета)
Currently, questions about digitalization, namely the digital transformation of the fuel and energy complex, are often raised in the Russian Federation. The relevance of the topic lies in the importance and necessity of introducing digital tools in the oil and gas industry. The arguments, substantiating the effects of digital transformation in the oil and gas complex are presented. The interpretation of the digital transformation of the Russian fuel and energy complex is given. The statistical data of the Ministry of Energy on the assessment of the total effect of digital transformation by 2035 are presented. The influence of digital technologies is analysed on the example of the oil and gas company Public Joint Stock Company “Lukoil”. The necessity of the National Infrastructure Investment Project, the importance of creating a center for hard-to-recover reserves and the introduction of an intelligent field are shown.